Running - Freeman, Lindsey A. (Book collections on Project MUSE., 2023)
"In Running, former NCAA Division I track athlete Lindsey A. Freeman presents the feminist and queer handbook of running that she always wanted but could never find. For Freeman, running is full of joy, desire, and indulgence in the pleasure and weirdness of having a body. It allows for a space of freedom-to move and be moved. Through tender storytelling of a lifetime wearing running shoes, Freeman considers injury and recovery, what it means to run as a visibly queer person, and how the release found in running comes from a desire to touch something that cannot be accessed when still. Running invites us to run through life, legging it out the best we can with heart and style."--